Self-Employment in the Light of Judicial Enforcement - Goles, Lucyna (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
From January 1, 2019. Amendments to the Code of Civil Procedure introduced by the Act of March 22, 2018 on Court Bailiffs apply. The legislator changed, inter alia, legal provision 8211 of the Code of Civil Procedure. The above amendment is intended to enable the debtor to conduct business while the enforcement proceedings are suspended. Under the current legal status, the debtor, who is, for example, an entrepreneur, despite the suspension of enforcement proceedings, was deprived of access to current funds in bank accounts, which could result in the cessation of business activity. The text is an attempt to discuss the motives of the amendment, as well as its effects. The analysis will cover the amended act and jurisprudence. 1 Dz.U. z 2018 r. poz. 771.